2015
DOI: 10.1590/1678-4499.0469
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytochemical contents in different parts of Clinacanthus nutans (Burm. f.) lindau due to storage duration

Abstract: Clinacanthus nutans is a well recognized medicinal herb for its high phytochemical contents. Several aspects may contribute to the phytochemical contents, and thus determine the quality and efficacy of an herb. An experiment was conducted using a completely randomized design (CRD) with five replications, in a factorial arrangement of treatments. including two plant parts harvested at two different stages such as young leaves, young stems, matured leaves and matured stems, and four different storage durations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 21 publications
3
20
0
2
Order By: Relevance
“…From the observation, C. nutans had been regularly being collected at the juvenile stage and the purpose of cultivation was for medicinal and research purposes. Thus, we had collected C. nutans at the juvenile stage (3 to 4 months) since a previous study had been conducted by Raya et al (2015) that showed younger leaves of C. nutans produced high DPPH radical scavenging activities and total flavonoid as well as high phytochemical contents than older leaves of C. nutans.…”
Section: Percentage Yield Crude Extractsmentioning
confidence: 99%
“…From the observation, C. nutans had been regularly being collected at the juvenile stage and the purpose of cultivation was for medicinal and research purposes. Thus, we had collected C. nutans at the juvenile stage (3 to 4 months) since a previous study had been conducted by Raya et al (2015) that showed younger leaves of C. nutans produced high DPPH radical scavenging activities and total flavonoid as well as high phytochemical contents than older leaves of C. nutans.…”
Section: Percentage Yield Crude Extractsmentioning
confidence: 99%
“…Another factor that may affect DPPH inhibition is extract storage duration. According to Raya et al (2015), DPPH inhibition of aqueous ethanolic extracts of C. nutans was drastically reduced by 69.97% from first day to four days of storage duration. Several other studies on DPPH inhibition have also been conducted.…”
Section: Phytochemical Constituents Of C Nutansmentioning
confidence: 99%
“…Furthermore, the influence of different plant parts, developmental storage and storage durations (1, 2, 3 and 4 days) [66], different temperature and sampling days [67], different storage days [68], Light (photosynthetically active radiation (PAR) level and maturity [69] examined to indicate that the there is no constant stability or dynamics of flavonoid content and its compounds in quantity and quality.…”
Section: Total Flavonoid Contentmentioning
confidence: 99%